The association of frontal sinus volume with traumatic brain injury - Sugumaren, Vengades @ Chee Siong A/L (2017)
Background: Brain injury is the major cause of death and hospital admission among Malaysian. It affects primarily younger generation and cost a lot of financial and man power cost. Paranasal sinuses are large area of aerated space anterior to the skull and around the face. There is not complete understanding to the function of the space yet. One of the theories of the function of the paranasal sinuses are as a crumble zone and impact absorber to reduce the injury to the brain . We would like to further explore this theory with this study. Objective: To study the association of frontal sinus volume with traumatic brain injury.Methodology: This is a cross sectional study from January 2016 till December 2016 (12 months) enrolling 126 patients who presented to the emergency and trauma centre regarding of trauma nature and sustained anterior impact indicated by frontal scalp swelling, facial bone or frontal bone fractures. All the patient underwent CT brain in Hospital Universiti Sains Malaysia. These non-contrast enhanced CT brain images were viewed and analyzed using Picture Archiving Communication System (PACS)application. The frontal sinus volume were measured with the OSIRIX application. The demographic data, brain injuries and frontal sinus measurements collected were analyzed using PASW Statistics 18 software. Result: The mean frontal sinus volume measured 9.35 +/- 4.74 cm3 disregarding of the gender. Considering gender, the mean frontal sinus volume for male is 8.75+/- 4.69 cm3, mean frontal sinus volume for female is 6.54 +/- 4.61 cm3. There is statistically significant association between the frontal sinus volume with traumatic brain injury, severity of brain injury, subdural bleed and subarachnoid bleed. Conclusion: Larger frontal sinus has protective effect on brain in traumatic event and reduce the severity of injury.